Flexible and Integrative Psychiatric Care Based on a Global Treatment Budget: Comparing the Implementation in Germany and Poland - Schwarz, Julian; Cechnicki, Andrzej; Godyń, Jan; Galbusera, Laura; Biechowska, Daria; Galińska-Skok, Beata; Ciunczyk, Izabela; Ignatyev, Yuriy; Muehlensiepen, Felix; Soltmann, Bettina; Timm, Jürgen; Peter, Sebastian von; et al. (Frontiers in Psychiatry, 2022)
Background: The past decade has witnessed the establishment of flexible and integrative treatment (FIT) models in 55 German and Polish psychiatric catchment areas. FIT is based on a global treatment budget (GTB), which integrates funding of all acute psychiatric hospital services for a regional population. Prior research has identified 11 specific program components of FIT in Germany. In this paper we aim at assessing the applicability of these components to the Polish context and at comparatively analysing FIT implementation in Poland and Germany. Methods: Qualitative interviews about the applicability of the 11 FIT-specific components were conducted with the program managers of the Polish FIT models (n=19). Semi-quantitative data on the FIT-specific components were then collected in 19 Polish and 10 German FIT models. We assessed the grading of each component, their overall degree of implementation and compared them between the two countries. In all study hospitals, structural and statistical parameters of service delivery were collected and compared. Results: The qualitative results showed that the German FIT-specific components are in principle applicable to the polish context. This allowed the comparative assessment of components grading and degree of implementation, which showed only subtle discrepancies between German and Polish FIT models. The little discrepancies point to specific aspects of care such as home treatment, peer support, and cooperation with non-clinical and social welfare institutions that should be further integrated in the components’ definition. Conclusions: The specific program components of FIT as first defined from the German experience, serves as a powerful tool to measure and evaluate implementation of integrated psychiatric care both within and between health systems.